Psychological distress within cardiovascular risks behaviors, conditions and diseases conceptual framework - Brborović, Ognjen (Array, 2009)
Summary: Psychological distress (PD) is being increasingly recognized as a risk factor for cardiovascular diseases (CVD). Our aim was to recognize an association of PD and CVD in the Croatian adult population. We also explored association’s strength obtainable as relative risk of PD on three levels; cardiovascular risk behaviors, conditions and diseases. This study used Croatian Adult Health Survey 2003 (CAHS 2003) data (N = 9,070). PD status was measured by the five-item Mental Health Scale of the Short Form questionnaire (SF-36) hence one distinguished subgroup consisted of population with PD and other without PD. Prevalence of cardiovascular risk behaviors, cardiovascular risk conditions and self-reported cardiovascular diseases within each subgroup were calculated using bootstrap method. Women had higher prevalence of PD in general population. Among distressed population women had higher prevalence of body mass index over 30, metabolic syndrome and angina pectoris. Men with PD had higher prevalence of high blood pressure and myocardial infarction with contradictory lower prevalence of angina pectoris then myocardial infarction. Physical inactivity was proven to be a risk behavior determinant with most impact on mental health. All CVD are consistently associated with higher prevalence and relative risks for PD both in men and women